Globalization and the Empowerment of Talent - Dalia Marin; Thierry Verdier (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2003)
Globalization has been identified by many experts as a new way firms organize their activities and as the emergence of talent as the new stakeholder in the firm. This paper examines the role of trade integration for the changing nature of the corporation. International trade leads to a 'war for talent' which makes it more likely that an organizational equilibrium emerges in the integrated world economy in which control is delegated to lower levels of the firms' hierarchy empowering human capital. Furthermore, trade integration is shown to lead to waves of outsourcing and to convergence in corporate cultures across countries.
urn:nbn:de:bvb:19-epub-268-0
Keywords: F12; F14; L22; D23; 330; international trade with endogenous organizations; the rise of human capital; theory of the firm; Rybczynski Theorem of firm organization